A STUDY OF MIXED-METHOD: SCIENCE PROCESS SKILLS, INTERESTS AND LEARNING OUTCOMES OF NATURAL SCIENCE IN JUNIOR HIGH SCHOOL - Yusnidar, Yusnidar; Fuldiaratman, Fuldiaratman; Chaw, Ei Phyu (LPPM Universitas Jambi, 2024)
This groundbreaking study unravels the intricate nexus between science process skills, learning interest, and student learning outcomes within natural sciences education. Adopting a pioneering mixed-method approach, this research transcends traditional boundaries by synergizing quantitative and qualitative methodologies to yield a multifaceted understanding of the underlying dynamics. Leveraging a purposive sampling technique, the study meticulously selects seventh-grade students and science teachers from junior high schools in the Batanghari district, positioning itself at the forefront of empirical inquiry into science education. Through a judicious blend of quantitative data analysis facilitated by sophisticated software and qualitative analysis of interactive interviews, the research unfurls a rich tapestry of insights. The findings underscore a compelling correlation between science process skills, learning interest, and learning outcomes, unveiling a nuanced interplay between these pivotal variables. The revelation that science process skills and learning interests collectively influence student learning outcomes is of particular significance, underscoring the holistic nature of science education. The novelty of this research lies in its holistic integration of three pivotal variables through a mixed-methods approach, engendering a deeper understanding of the complex dynamics at play. This study paves the way for a more comprehensive comprehension of the factors shaping science education outcomes by transcending the limitations of singular methodological approaches. Ultimately, the insights gleaned from this research hold profound implications for educational practice, highlighting the imperative of fostering science process skills and nurturing learning interest to optimize student learning outcomes in natural sciences education.